2006
DOI: 10.1111/j.1747-6593.2006.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane performance enhancer evaluations on pilot‐ and full‐scale membrane bioreactors

Abstract: Recently developed polymeric membrane performance enhancer product, MPE50, was tested in various pilot-and full-scale membrane bioreactors (MBRs). The Initial MPE50 dosage was determined by visual jar tests and by using various bench-top filtration tests. Different amounts of MPE50 were dosed, and the particle size and supernatant clarity of the mixed liquor were monitored visually. Bench-top filtration tests were also conducted. A 50% higher MPE50 dosage is recommended to be added to the pilot/full-scale bior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…They are easily accumulated, causing poor filterability of the sludge suspension (Drews et al, 2008;Juang et al, 2013). In general, the fouling rate can controlled using two approaches: (i) the regulation of operational parameters, such as sludge retention time (SRT), hydraulic retention time (HRT), dissolved oxygen (DO) concentration, temperature, aeration, and (ii) the addition of certain chemicals which modify the characteristics of the mixed liquor upon coagulation (Guo et al, 2010;Koseoglu et al, 2008;Wu et al, 2006;Zhang et al, 2008), flocculation (Collins et al, 2006;Guo et al, 2010;Ji et al, 2010;Wozniak, 2010) or adsorption (Le-Clech et al, 2006;Meng et al, 2009). These chemical agents include organic polymers (Vera Iversen et al, 2009;Koseoglu et al, 2008) and inorganic flocculants, such as aluminium and ferric chloride (Koseoglu et al, 2008;Wu et al, 2006;Yu et al, 2016), which in general improve the sludge filterability but at the expense of an increase cost (Huyskens et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They are easily accumulated, causing poor filterability of the sludge suspension (Drews et al, 2008;Juang et al, 2013). In general, the fouling rate can controlled using two approaches: (i) the regulation of operational parameters, such as sludge retention time (SRT), hydraulic retention time (HRT), dissolved oxygen (DO) concentration, temperature, aeration, and (ii) the addition of certain chemicals which modify the characteristics of the mixed liquor upon coagulation (Guo et al, 2010;Koseoglu et al, 2008;Wu et al, 2006;Zhang et al, 2008), flocculation (Collins et al, 2006;Guo et al, 2010;Ji et al, 2010;Wozniak, 2010) or adsorption (Le-Clech et al, 2006;Meng et al, 2009). These chemical agents include organic polymers (Vera Iversen et al, 2009;Koseoglu et al, 2008) and inorganic flocculants, such as aluminium and ferric chloride (Koseoglu et al, 2008;Wu et al, 2006;Yu et al, 2016), which in general improve the sludge filterability but at the expense of an increase cost (Huyskens et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A recent study cited the use of membrane performance enhancers (MPE) (a polyelectrolyte-based flocculant recently developed by Nalco) in full-and pilot-scale MBR plants. When the MPE was dosed at 400 mg=L, the average membrane flux was reported to increase by 50-178% and the supernatant polysaccharide level reduced in the mixed liquor in the long-term operation of a pilot-scale MBR (5,18,19).…”
Section: Introductionmentioning
confidence: 97%
“…''Critical flux'' is mainly controlled by the small particles in the mixture. Below the critical flux, no particles deposit on the membrane and above the critical flux, particles deposit on the membrane due to the transmembrane pressure (TMP), and may become irreversible foulants (4,5). It is recognized that in MBRs the concept of ''critical flux'' is debatable, as some degree of fouling appears to occur at any flux (6).…”
Section: Introductionmentioning
confidence: 99%
“…Lab and pilot scale experiments with MPE50 addition have shown that the membrane fouling rates could significantly be reduced even under high flux conditions and the process could be operated at an extremely high suspended solid level, e.g. 50,000 mg/L [10]. In addition, permeate chemical oxygen demand (COD) was improved by approximately 30%, whereas no toxic effects on bioactivity were found.…”
Section: Introductionmentioning
confidence: 98%